KOMBINASI TENS DAN CORE STABILITY EXERCISE MENGURANGI NYERI DAN MENINGKATKAN KEKUATAN OTOT PADA PASIEN SPONDYLOSIS LUMBAL - Pabuaran, Birgiana; Mamuaja, Filly; Geneo, Martinus; Eman, Friets (Lasalle Health Journal, 2025)
Introduction: As age increases, the risk factors for experiencing lower back pain also increase. In addition, the length of time and duration of work also play a role in causing lower back pain. Lower back pain is also caused by degeneration of the discs and facet joints in the spine, especially in the lumbar region, which can lead to pressure on the intervertebral foramen resulting in osteophyte formation that can cause irritation and pain. This condition is referred to as lumbar spondylosis. Lumbar spondylosis is a degenerative condition that can cause chronic pain in the back, characterized by abnormal bone growth or osteophytes, thinning of the intervertebral discs, and narrowing of the space between vertebrae, which leads to pain and functional disturbance in the lower back. Objective: to evaluate the effectiveness of the combination of TENS and core stability exercise in reducing pain and increasing muscle strength in patients with lumbar spondylosis. The method used in this study is a case study of a patient diagnosed with lumbar spondylosis to undergo TENS intervention and core stability exercises for six therapy sessions, conducted twice a week. The results of the study indicate that the combination of TENS and core stability exercise resulted in a decrease in pain using the VAS scale and an increase in lumbar muscle strength. Keywords: Core stability exercise, TENS, Lumbar spondylosis.